MODELING IN LAW AS A WAY OF UNDERSTANDING LEGAL PHENOMENA - D. G. Trinitka (Теоретическая и прикладная юриспруденция, 2022)
This article substantiates the need to apply such a scientiﬁc method as modeling in the legal sphere. The concept of modeling is revealed as a hypothetical construction used to build assumptions in law enforcement, as well as a post-event reﬂection of existing phenomena of legal reality. An analysis of the methodological principles on which legal modeling is based is presented. The author focuses on the philosophical and legal dimension of models, which makes it possible to base not only the teleological aspect of the application of models, but also the subjective-rational one. The rationale for the increment of scientiﬁc legal knowledge with the help of such a subspecies of scientiﬁc modeling as a legal reasoning is presented. Based on this study, the author substantiates the necessary relationship between theory and practice in jurisprudence, from the synergy of which modeling in law grows.